2016
DOI: 10.2340/16501977-2121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early mobilization and rehabilitation on global functional outcome one year after aneurysmal subarachnoid hemorrhage

Abstract: Objective: To assess the impact of early mobilization and rehabilitation on global functional outcome one year after aneurysmal subarachnoid haemorrhage. Methods: Prospective, controlled, interventional study comprising patients managed in the neuro-intermediate ward following repair of a ruptured intracranial aneurysm. Patients in the Control group (n = 76) received standard treatment, whereas those in the Early Rehab group (n = 92) in addition underwent early mobilization and rehabilitation. Demographic, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
0
25
0
5
Order By: Relevance
“…Another Swedish study has shown similar results in a stroke population, with treatment in a rehabilitation ward unit as an unfavourable factor for RTW (29). An interventional study, however, has reported that early mobilization and rehabilitation increases the probability of good functional outcome (30).…”
Section: Discussionmentioning
confidence: 76%
“…Another Swedish study has shown similar results in a stroke population, with treatment in a rehabilitation ward unit as an unfavourable factor for RTW (29). An interventional study, however, has reported that early mobilization and rehabilitation increases the probability of good functional outcome (30).…”
Section: Discussionmentioning
confidence: 76%
“…Consequently, in order to avoid re-bleeding, especially for patients who have not had, or could not have, surgical or endovascular treatment for the aneurysm, bed-rest for 4-6 weeks is often included as a component of the treatment strategy (31,32). Conversely, in patients with SAH, the feasibility and safety of arterial and intracranial pressure of an early rehabilitation programme was focused on functional training and therapeutic exercise in more progressively upright positions (33,34). How ever, a recent Cochrane systematic review concluded that no randomized controlled trails or controlled trials were available to provide evidence for or against staying in bed for at least 4 weeks after symptom onset, and suggested further research to clarify optimal periods of bed-rest for these patients (32).…”
Section: Discussionmentioning
confidence: 99%
“…Revisões bibliográficas, resumos, relatos de casos, estudos qualitativos ou sem informações sobre a amostragem e análise efetuada, estudos desenvolvidos durante a fase de reabilitação ambulatorial e publicações anteriores ao ano de 2012, foram excluídos. (5,8,(12)(13) , dois trazem evidências de que o tratamento convencional é mais seguro (6,10) , e apenas um é inconclusivo em relação a ocorrência de complicações graves ou melhora funcional atribuídos a mobilização precoce em pacientes após AVC (7) . Um estudo afirma que a intervenção por meio da mobilização precoce ainda é mal definida e não apoiada por fortes evidências.…”
Section: Materials E Métodounclassified
“…Pacientes com AVC grave e aqueles com hemorragia intracerebral apresentam menos chance de um resultado favorável em três meses se tratados com o protocolo de mobilização precoce (6) . Diante disso, em uma análise retrospectiva, foi mencionada uma preocupação quanto à possibilidade de uma re-hemorragia, afetando negativamente o desenvolvimento e o curso do vasoespasmo cerebral (13) . Em contrapartida, outro autor concluiu que o exercício leve reduz este vasoespasmo e a reabilitação precoce é considerada segura e viável após hemorragia subaracnóidea aneurismática, por exemplo (14) .…”
Section: Materials E Métodounclassified
See 1 more Smart Citation